Relation between non-alcoholic fatty liver disease and ischemic heart disease studied at rural tertiary care centre in Uttar Pradesh, India - Kumar, Granth; Vaishya, Ganga Prasad; V., Vijayavarman; Ahmad, Saleem; Kumar, Pawan; Kumar, Rahul (International Journal of Research in Medical Sciences, 2020)
Background: Non-alcoholic fatty liver disease (NAFLD) is the leading cause of chronic liver disease in the United States and other industrialized countries, many study has identified NAFLD as a risk factor not only for premature coronary artery disease and cardiovascular events, but also for early subclinical abnormalities in myocardial structure and function. Aim of this study was to the presence of NAFLD in patients with Ischemic Heart Disease (IHD) and Relation of NAFLD with other risk factors of IHD. Methods: The study group consisted of 150 patients that comply with inclusion criteria and selected of 100 consecutive patients who underwent coronary angiographies. Coronary artery disease was defined as a stenosis at least 50% in at least one major coronary artery. Fatty liver was diagnosed by abdominal ultrasonography (4 stages: Grades 0, 1, 2 and 3). Statistical evaluations were performed using T test, Chi- square test. Results: The present study was done in 100 patients of coronary artery disease divided into two groups i.e. Non NAFLD group n= 62 (62%) and NAFLD group n= 38 (38%). The present study shows that the prevalence of NAFLD was highest (86.8%) in more than 40 years of age group. The present study shows that the prevalence of NAFLD was more in males (84.2%) as compare to females (15.8%). The present study also shows significantly high incidence of metabolic syndrome in patients with NAFLD (23.7%) as compared to Non-NAFLD (3.2%) patients with Coronary Artery (CAD). Conclusions: The presence of fatty liver and its severity should be carefully considered as independent risk factors for IHD. The study results suggest the synergistic effect in between fatty liver and deranged lipid profile for developing IHD. Abdominal ultrasonography may provide valuable information about IHD risk assessment.